Functional rescue of the glomerulosclerosis phenotype in Mpv17 mice by transgenesis with the human Mpv17 homologue - Schenkel, Johannes; Zwacka, Ralf Michael; Rutenberg, Christiane; Reuter, Alexander; Waldherr, Rüdiger; Weiher, Hans (Kidney international, 1995)
Functional rescue of the glomerulosclerosis phenotype in Mpv17 mice by transgenesis with the human Mpv17 homologue. The germ line insertion of a defective retrovirus into the Mpv17 gene of mice is associated with a recessive phenotype. Mice homozygous for the integration develop glomerulosclerosis at a young age. The phenotype resembles human glomerulosclerosis in its physiological parameters as well as in histology. A human homologue of the Mpv17 gene has been identified, isolated and analyzed. We here show that this gene, which has a role in the production of reactive oxygen species, can rescue the phenotype of Mpv17 deficient mice when introduced by transgenesis. This provides formal proof for the hypothesis that the phenotype is caused by the loss of function of the Mpv17 gene. It also provides evidence for the functional conservation of the Mpv17 gene in mammals and points to a potential role of this gene in human kidney disease.